Simulation of Body Surface Laplacian Maps during Ventricular Pacing in a 3D Inhomogeneous Heart-Torso Model - Wu, D.; Ono, K.; Hosaka, H.; He, B. (Methods of Information in Medicine, 2000)
A computer simulation study has been conducted to investigate the performance of body surface Laplacian maps (BSLMs) in localizing and imaging spatially separated myocardial electrical events. A cellular automaton model of ventricles simulates cardiac electrical activity using a two-site pacing protocol to induce dual simultaneously active myocardial electrical events. The heart model is embedded in a realistically shaped inhomogeneous volume conductor. The BSLMs are numerically computed from the induced electrical activity in the heart model. The present computer simulation results show that the BSLM can provide better separation and localization of two regional myocardial electrical events as compared with the body surface potential map (BSPM).
Keywords: Body Surface Laplacian Mapping; Heart Model; Electrocardiography; Computer Modeling